Sleep and productivity benefits of digital cognitive behavioral therapy for insomnia: a randomized controlled trial conducted in the workplace environment - Bostock, S; Luik, A; Espie, C (Lippincott, Williams & Wilkins, 2016)
Evaluating digital cognitive behavioral therapy (dCBT) for insomnia in a workplace environment.Within a randomized controlled trial in a Fortune 500 company, we randomized 270 self-identified poor sleepers [180 M/90 F: mean age 33.6 years (23 to 56 years)] to dCBT (n = 135) or waiting list (WL, n = 135). dCBT comprised six online sessions delivered by an animated therapist. Major assessments were at baseline and posttreatment.Sleep Condition Indicator (SCI) scores were significantly higher for the dCBT group [interaction term: F (1,485) = 15.63, P < 0.0001], representing Cohen's d of 1.10 following dCBT (d = 0.34 for WL). On the Work Productivity and Impairment questionnaire, "presenteeism" demonstrated significant improvements following dCBT [F(1,485) = 10.99, P = 0.001: d = 0.64 for dCBT, d = 0.09 for WL]. Effects for "abseenteeism" failed to reach statistical significance (P = 0.101).dCBT is effective in improving sleep and work-based productivity in adults with insomnia.